2019
DOI: 10.1101/688580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intestinal delta-6-desaturase activity determines host range forToxoplasmasexual reproduction

Abstract: Many eukaryotic microbes have complex lifecycles that include both sexual and asexual phases with strict species-specificity. While the asexual cycle of the protistan parasite Toxoplasma gondii can occur in any warm-blooded mammal, the sexual cycle is restricted to the feline intestine 1 . The molecular determinants that identify cats as the definitive 5 host for T. gondii are unknown. Here, we defined the mechanism of species specificity for T.gondii sexual development and break the species barrier to allow t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Reports on T. gondii endopolygeny suggest geometric expansion of nuclei: 8-16 progeny per endopolygeny replication cycle in the cat gut have been observed (Ferguson et al, 1974). Historically, the sexual cycle of T. gondii has been poorly experimentally accessible, but in vitro completion of the sexual cycle in cat intestinal organoids was recently reported, which is expected to provide experimental accessibility (Martorelli Di Genova et al, 2019). To date, T. gondii endopolygeny studies have not been so comprehensive to support a strong conclusion in this matter.…”
Section: Endopolygeny With Karyokinesismentioning
confidence: 99%
“…Reports on T. gondii endopolygeny suggest geometric expansion of nuclei: 8-16 progeny per endopolygeny replication cycle in the cat gut have been observed (Ferguson et al, 1974). Historically, the sexual cycle of T. gondii has been poorly experimentally accessible, but in vitro completion of the sexual cycle in cat intestinal organoids was recently reported, which is expected to provide experimental accessibility (Martorelli Di Genova et al, 2019). To date, T. gondii endopolygeny studies have not been so comprehensive to support a strong conclusion in this matter.…”
Section: Endopolygeny With Karyokinesismentioning
confidence: 99%
“…Demand for heme in sexual stages will depend on how these stages generate energy as well as on the availability of heme in the cat gut environment. Recent, elegant studies suggest that these stages may become more tractable in the future [42,43], opening the possibility for these questions to be addressed.…”
Section: Heme Demand In Protozoan Parasitesmentioning
confidence: 99%
“…Breakthrough work by Martorelli Di Genova and colleagues, approached a long-standing mystery in the field: what is the biochemical footprint that makes felines the selected definitive host? Briefly, the authors identified that host-specificity to felines in the sexual stage is owed to the accumulation of linoleic acid, given by the lack of delta-6-desaturase activity in their intestines, ( Di Genova et al., 2019 ). Felines are the only mammals that lack this enzyme activity in their intestines.…”
Section: Molecular and Structural Links Between Asexual And Sexual Rementioning
confidence: 99%
“…Felines are the only mammals that lack this enzyme activity in their intestines. Remarkably, inhibiting this enzyme’s activity alone, and supplementing mice diet with an excess of linoleic acid, allowed them to now become T. gondii infectious oocyst spreaders ( Di Genova et al., 2019 ).…”
Section: Molecular and Structural Links Between Asexual And Sexual Rementioning
confidence: 99%